Features of the Implementation of the Concept of Managing Decent Work Conditions at Small and Medium-Sized Enterprises in the Construction Industry - К. V. Gileva (Управленческие науки, 2024)
In modern conditions, the development of any industry directly depends on the provision of highly qualified labor resources. Due to the constant shortage of personnel, it is important for employers to implement systematic measures to attract, retain and optimally use the required specialists of various qualifications. It is these tasks that the enterprise solves when organizing personnel work in accordance with the basic principles and ideas of decent work. The construction industry in the Russian Federation is one of the most dynamically developing, making a significant contribution to the country’s GDP, but companies from this sector are faced with a global shortage of both labor and highly qualified specialists. It should also be noted that this sector is considered to be one of the most hazardous, injury-prone and requiring increased attention to occupational and labor safety. The purpose of the study is to identify a set of external and internal factors that determine the features of decent work management at enterprises in the construction industry. To achieve this goal, the methods of interdisciplinary analysis of scientific literature and the regulatory framework, economic analysis and analytical statistics were used. The application of counter modeling made it possible to decompose the theoretical model of decent work management and highlight the real conditions of the production, financial and socio-economic activities of enterprises in the construction complex. The results of the study are related to identifying the role of government policy, the labor market, general trends in the construction industry, vocational professional education, as well as personnel policies within the organization in the process of implementing the concept of decent work. The conclusions drawn may be of interest to managers of construction companies, and human resources and personnel management services for analyzing their own practices and carrying out measures to introduce the principles of decent work at individual enterprises in this economic sphere.